Materials science and manufacturing engineering : selected peer-reviewed papers from the 3rd International Conference on Materials Science and Manufacturing Engineering (MSME 2020) : selected, peer-reviewed papers from the International Conference on Materials Science and Manufacturing Engineering (MSME 2020), November 5-8, 2020, Sanya, China - Chen, Zhanwen, Prof (Materials science forum ;, 2021)
This issue is a collection of peer-reviewed papers in the area of materials science and materials processing technologies presented at the 3rd International Conference on Materials Science and Manufacturing Engineering (MSME 2020) was held in Sanya, China, during November 5-8, 2020, in a combination of online and offline. Alloy, Superalloy, Composites, Polymers, Metal Oxide, Ceramics, Semiconductor, Nanomaterials, Mechanical Properties, Photocatalytic Activity, Additive Manufacturing, Milling, Welding, Cutting, Surface Engineering, Coatings, Laser Processing, Plasma Cladding Materials Science, Mechanical Engineering, Bioscience and Medicine.